Digitalisasi Pengembangan Sistem KKN Universitas Pancasakti Tegal Berbasis GIS Menggunakan Metode Prototyping - Didiek Trisatya (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
Universitas Pancasakti Tegal is a private university in Central Java. Among them is the existence of an obstacle regarding the manual registration process for participants, not knowing the location points for administering KKN at universities for students, the absence of reporting of location points for the KKN village area for Lecturer Field Supervisors (LFS) and the KKN committee conducting the search the shortest way to find an important location, the location for administering the KKN, and filling out the KKN implementation schedule based on the location where it has not been digitalized so that the KKN implementation has not been managed effectively. Therefore, designing an Online KKN system is necessary to replace the manual system. By using the prototyping method, a prototyping system is produced that acts to connect developers with users to interact with each other in the continuity of information system development. The research results were obtained by applying API maps in the Online KKN system using Mapbox GL JS v2.11.0 to help access locations and applying markers as markers for a location as well as applying algorithms to solve the problem of finding the shortest route from the starting point to the endpoint using the Dijkstra algorithm.